Analisis Tren Lifestyle “Skena” Dalam Kerangka Sosial Budaya Pada Era Modern - Halimah Nur Churil Aini; Meydina Tri Luvianasari; Maris Jennet Landicho; Selvia Deva Saputri (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
Life in the modern era is characterized by rapid lifestyle changes, including the 'skena' trend that becomes an integral part of student culture at the University of Jember. This research aims to analyze the lifestyle trend "skena" in the socio-cultural framework in the modern era, with a focus on Jember University students as a case study. A qualitative approach is used to collect and analyze data through in-depth interviews and participatory observations. The results show that the 'skena' trend reflects patterns of behavior, values, and norms that develop in student society. Social and cultural factors such as technology, globalization, identity, and self-expression play an important role in shaping and influencing these trends. This research provides an in-depth understanding of the phenomenon of "skena" and its implications for student culture at the University of Jember and provides a foundation for further research on lifestyle trends in the socio-cultural context.